SISTEM INFORMASI KANTOR CAMAT RATU SAMBAN KOTA BENGKULU BERBASIS WEB - Siswanto, Siswanto; Zulita, Leni Natalia; yono, Hari Aspri (Jurnal Media Infotama, 2012)
Technology progressively expand along with the increasing of requirement in entering globalization world, we recognize technology which progressively go forward to water down to conduct various activity in life, for example progress in transportation area, communications, health, education, and other area represent example of that us progressively need technology in this lifePursuant to existing problem is how How to make officer information system at queen sub-regency chief office of samban Town of Bengkulu and How to use Ianguage of Pemograman PHP, Macromedia Dreamweaver, Mysql.From result of examination of system, can improve officer information efficiency, and have separate excellence in giving information to all officerKeyword : Information System, Website